2017
DOI: 10.1007/s10519-017-9884-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variance in Homophobia: Evidence from Self- and Peer Reports

Abstract: The present twin study combined self- and peer assessments of twins' general homophobia targeting gay men in order to replicate previous behavior genetic findings across different rater perspectives and to disentangle self-rater-specific variance from common variance in self- and peer-reported homophobia (i.e., rater-consistent variance). We hypothesized rater-consistent variance in homophobia to be attributable to genetic and nonshared environmental effects, and self-rater-specific variance to be partially ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The heritability estimates produced by the models incorporating peer data were substantially lower, and nonshared environmental influences were higher. Heritability estimates for social attitudes do tend to be lower in peer- versus self-report studies, 79,80 but the magnitude of the difference across measurement types was contrary to expectation and gives one pause when interpreting previous work on liberalism/conservatism.…”
Section: Discussionmentioning
confidence: 92%
“…The heritability estimates produced by the models incorporating peer data were substantially lower, and nonshared environmental influences were higher. Heritability estimates for social attitudes do tend to be lower in peer- versus self-report studies, 79,80 but the magnitude of the difference across measurement types was contrary to expectation and gives one pause when interpreting previous work on liberalism/conservatism.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to the strict social sciences’ point of view, the heritability estimates for political opinions and ideologies—including broad political orientations, such as conservatism (Jost, 2006), right-wing authoritarianism (Altemeyer, 1996), and social dominance orientation (Pratto, Sidanius, Stallworth, & Malle, 1994), or specific political opinions, such as attitudes toward homosexuals—range from moderate to high (Alford, Funk, & Hibbing, 2005; Bell, Schermer, & Vernon, 2009; Kandler, Bell, & Riemann, 2016; Zapko-Willmes & Kandler, 2018). However, it has been argued that the closeness to a certain party might be more environmentally influenced than individual differences in political attitudes in general.…”
Section: Behavior Genetic Research On Political Orientation and Party...mentioning
confidence: 98%
“…All measurable human differences have genetic correlations. Researchers have found that income, marital status, health insurance coverage, homophobia, military service, frequency of bread eating, and dog ownership are all heritable (Beaver et al, 2015; Fall et al, 2019; Hasselbalch et al, 2010; Hyytinen et al, 2019; Trumbetta et al, 2007; Wehby & Shane, 2019; Zapko-Willmes & Kandler, 2018). Obviously, human genes do not code for whether someone enrolls in health care coverage or joins the military.…”
Section: Claim 4 Hitop Will Lead To Genetic Discoverymentioning
confidence: 99%